2006
DOI: 10.1016/j.joca.2005.10.005
|View full text |Cite
|
Sign up to set email alerts
|

Raised chondroitin sulfate epitopes and hyaluronan in serum from rheumatoid arthritis and osteoarthritis patients

Abstract: CS epitopes WF6 and 3B3 (+) are raised in serum of patients with both OA and RA and were thus distinct from serum HA. The results suggest that OA may be detected systemically as well as RA. The range of levels of CS epitopes detected in OA and RA was wide and correlation with any aspect of disease activity is yet to be determined.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
40
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(42 citation statements)
references
References 14 publications
2
40
0
Order By: Relevance
“…It has recently been demonstrated that a single chain phage display antibody GD3G7 also interacts with multiple decasaccharide sequences isolated from squid cartilage CS-E (63). Although the octasaccharides and the saturated counterparts (D-C-C-C and C-C-A-D), which were recognized by WF6, were isolated in this and previous studies (55) from shark cartilage CS chains, the epitopes are present in humans, since elevated levels of the epitopes have been detected by WF6 in sera from patients with osteoarthritis, rheumatoid arthritis (19), and ovarian cancers (20). In view of the findings that the above described antibodies, including WF6, interact with multiple oligosaccharides containing similar yet distinct sequences, we used molecular modeling to investigate possible common features shared by the preferred octasaccharides and absent from the nonpreferred octasaccharides.…”
Section: Tablementioning
confidence: 64%
See 1 more Smart Citation
“…It has recently been demonstrated that a single chain phage display antibody GD3G7 also interacts with multiple decasaccharide sequences isolated from squid cartilage CS-E (63). Although the octasaccharides and the saturated counterparts (D-C-C-C and C-C-A-D), which were recognized by WF6, were isolated in this and previous studies (55) from shark cartilage CS chains, the epitopes are present in humans, since elevated levels of the epitopes have been detected by WF6 in sera from patients with osteoarthritis, rheumatoid arthritis (19), and ovarian cancers (20). In view of the findings that the above described antibodies, including WF6, interact with multiple oligosaccharides containing similar yet distinct sequences, we used molecular modeling to investigate possible common features shared by the preferred octasaccharides and absent from the nonpreferred octasaccharides.…”
Section: Tablementioning
confidence: 64%
“…It is reactive with shark CS-PGs, and the epitope was also detected in commercial CS preparations (CS-C and CS-D) from shark cartilage, but the antibody is unreactive with other glycosaminoglycans (GAGs) (25). An enzyme-linked immunosorbent assay (ELISA) has shown that this mAb detected an increased level of WF6 epitope in serum samples from patients of osteoarthritis and rheumatoid arthritis (19) and in those of ovarian cancer (20). The established specificity of the antibody and its restricted distribution among CS chains has suggested that the epitope is a specific sequence found in some but not all CS chains and is composed of sulfated disaccharides, including A unit (GlcUA␤1-3GalNAc(4-O-sulfate)), C unit (GlcUA␤1-3GalNAc(6-O-sulfate)), and D unit (GlcUA(2-O-sulfate)␤1-3GalNAc(6-O-sulfate)).…”
mentioning
confidence: 99%
“…More sophisticated determination of chondroitin sulphate (CS) epitope WF6 was also done in both OA and rheumatoid arthritis patients. However, as the levels of both HA and WF6 were elevated in patients with these two diseases, a strict correlation with disease activity was not fully validated [116]. As the involvement of bone tissue was also becoming recognised in the initiation and/or progression of OA, biochemical markers of bone turnover were also determined in some clinical studies.…”
Section: Bone Markers In Oamentioning
confidence: 99%
“…Several factors are considered for the pathogenesis of kOA [6][7][8][9][10][11][12][13][14]. Complicated path biological interactions between the KallikreinKinin System (KKS), the Rennin-Angiotensin (RAS), angiogenesis and natural immunity could contribute to joint destruction in the disease process of kOA [15][16][17][18][19].…”
Section: Identification Of Circulating Natural Antibodies Against Endmentioning
confidence: 99%